Species Diversity of Grasshopper (Orthoptera: Caelifera) at the Rehabilitation Zone of the Bonangan Block, Wonoasri Resort, Meru Betiri National Park - Setiawan, Rendy; Siddiq, Arif Mohammad; Ananda, Mia Bella Dwy (Universitas Jember, 2023)
Grasshoppers (Caelifera) are herbivorous insects that act as first consumers in the food chain. Grasshoppers can detect the presence or absence of plants as a source of food and a place to live, as well as being an indicator of environmental recovery. This study aims to determine the diversity of grasshopper species in the rehabilitation zone of Bonangan Block, Resort Wonoasri Meru Betiri National Park. The sampling method used a structured roaming technique. The results obtained nine types of grasshoppers covering seven genera with a total of 228 individuals. The diversity index value obtained is 1.86. The conclusion of this study was that the composition of grasshoppers included nine types of grasshoppers found, namely Oxya sp., Catantops sp., Trilophidia sp. (1), Trilophidia sp. (2), Schistocerca sp., Acrida sp., Phlaeoba sp., Atractomorpha sp. (1) and Atractomorpha sp. (2). The value of the diversity index of grasshoppers is in the medium category with the diversity index value of 1.86.